Regulation effect of slit-check dam against woody debris flow: Laboratory test - Xie, Xiangping; Wang, Xiaojun; Liu, Zhenzhen; Liu, Zhixuan; Zhao, Shenzhou (Frontiers in Earth Science, 2023)
Woody debris flows (i.e., debris flows carrying wood) are common in mountainous and forested areas. They can cause more severe hazards due to the effects of LW (woody debris larger than 1 m in length and 10 cm in width) compared to debris flows without LW. Mitigation structures for debris flows have considered little of the regulating effect on LW and the influence of LW on the regulation effect of sediment. Thus, model tests were conducted to discuss the regulation effects of slit-check dams on woody debris flow. Research results demonstrated that slit-check dams can effectively regulate woody debris flows without overflows. Once overflow occurs, sediment trapping efficiency and the wood retention rate dramatically decrease. The sediment trapping efficiency of slit-check dams on debris flows without LW shared a linear relationship with the relative opening width, the height-to-width ratio of the opening, and the opening density. However, this was also influenced by the wood retention rate for woody debris flow. A logarithmic relationship between the sediment trapping rate and wood retention rate was obtained. The wood retention rate is mainly determined by the ratio of the LW length to the opening width, the ratio of the LW length to the channel width and the opening density of the slit-check dam. Three draining patterns of woody debris flows at the slit-check dam and three clogging types of LW at the openings of the slit-check dam were observed. Some design criteria for the structure parameters of the slit-check dam were proposed. These research results promote a better understanding of the regulation effect of slit-check dams on woody debris flows and provide a basis for the optimal design of slit-check dams.